Saint Bernadette Soubirous : 1844-1879 - Trochu, Francis, 1877- ([New York] Pantheon, 1957)
b
Keywords: Bernadette, Saint, 1844-1879.; Apparitions -- Biography; Bernadette, Saint, 1844-1879 -- Biography; Lourdes, Our Lady of -- Biography; Mary, Blessed Virgin, Saint Apparitions and miracles France -- Biography